A Survey on Cloud Computing Scheduling Algorithms - Meriam, Essaies; Tabbane, Nabil (2016 Global Summit on Computer & Information Technology (GSCIT), 2016)
Cloud computing is a distributed computing modelwhich enables developers to automatically deploy applicationsduring task allocation and storage distribution. Cloud computingintends to share a pool of virtualized computer resources andequipment's of computation, storage and information. In cloudcomputing environment, task scheduling is a key problem whichneeds to consider various factors restricting the user tasks and isresponsible for selecting the most suitable resources of cloudcomputing for user task. Task scheduling algorithm is an NPcompleteproblem which places an important role in cloudcomputing. This article surveys the literature on job schedulingalgorithms as they apply to cloud computing environment. Itsummarizes keys of performance of each algorithm in different loadstates from conducted simulation.